(untitled) (World Conference on Engineering and Technological Sciences, 2026)
This article examines the role of information and communication technologies in developing the aesthetic culture of future teachers. It explores the essence of individual aesthetic culture, the specifics of its development in the context of digitalization of education, and the potential of modern information and communication technologies for developing the artistic taste, aesthetic worldview, and creative potential of students majoring in teaching. Particular attention is paid to the use of multimedia, electronic educational resources, virtual museums, and interactive learning technologies.